2018
DOI: 10.21037/jss.2018.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative drain use in patients undergoing decompression and fusion: incidence of complications and symptomatic hematoma

Abstract: Our study suggests that the use of postoperative subfascial drains in patients undergoing spinal decompression with fusion may not be associated with a reduction in SSIs or hematoma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…24 , though stated as a RCT, is a cohort study by described methodology and thus assessed as such. Of the cohort studies, 26 (81.2%) were retrospective 9,[13][14][15]17,20,22,23,[25][26][27][29][30][31][33][34][35][36][37][38]40,41,44,46,47,49 , 3 (9.4%) were prospective 16,21,24 , and 3 (9.4%) was ambispective 12,43,48 in study design. The number of patients in included RCTs ranged from 30 to 326 (Median: 155), whilst that in cohort studies ranged from 42 to 10,225 (Median: 265.5).…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 , though stated as a RCT, is a cohort study by described methodology and thus assessed as such. Of the cohort studies, 26 (81.2%) were retrospective 9,[13][14][15]17,20,22,23,[25][26][27][29][30][31][33][34][35][36][37][38]40,41,44,46,47,49 , 3 (9.4%) were prospective 16,21,24 , and 3 (9.4%) was ambispective 12,43,48 in study design. The number of patients in included RCTs ranged from 30 to 326 (Median: 155), whilst that in cohort studies ranged from 42 to 10,225 (Median: 265.5).…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…The number of patients in included RCTs ranged from 30 to 326 (Median: 155), whilst that in cohort studies ranged from 42 to 10,225 (Median: 265.5). 17 of 30 12,15,18,21,22,[24][25][26]31,32,35,40,42,43,45,47,48 There is insufficient evidence to provide recommendations on postoperative AMP administration to reduce the rate of SSI in other types of spine surgery.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the above-mentioned results, Adogwa et al concluded that the use of drains was not associated with a reduction of SSIs in patients undergoing spinal decompression and fusion [18]. In a retrospective clinical study of 133 patients who underwent primary spinal surgery (37 laminoplasties, 16 decompressions, 80 fusions), there was no significant association between drain tip culture and drainage duration, or between the rate of SSI and drainage duration [19].…”
Section: Duration Of Treatment With Suction Drainagementioning
confidence: 84%